2016
DOI: 10.1111/mcn.12402
|View full text |Cite
|
Sign up to set email alerts
|

Health staff understanding, application, and interpretation of growth charts in Nigeria

Abstract: 43We aimed to compare plotting accuracy and interpretation of weight gain patterns in average 44 and small infants on Road-to-Health (RTH) and the new WHO growth charts in Enugu, 45Nigeria. Child health staff plotted standard weights on both formats. Twelve plotted charts 46 were created, permutating 3 different weight trajectories (fast, steady, slow) ending at two 47 attained weights (average, small), with each plotted on both chart formats. Respondents 48 were shown four of these charts and asked to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our intervention was not associated with an improvement in growth monitoring accuracy. Improving growth monitoring interpretation accuracy has been found to be difficult in other studies (Mutoro & Wright, 2013) and might be explained by the quality of training or even the experience in practicing interpretation (Ezeofor et al, 2017). Our study was conducted at both hospitals and health centres, and inaccuracy in the interpretation may be due to the lack of familiarity and level of training of the staff.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our intervention was not associated with an improvement in growth monitoring accuracy. Improving growth monitoring interpretation accuracy has been found to be difficult in other studies (Mutoro & Wright, 2013) and might be explained by the quality of training or even the experience in practicing interpretation (Ezeofor et al, 2017). Our study was conducted at both hospitals and health centres, and inaccuracy in the interpretation may be due to the lack of familiarity and level of training of the staff.…”
Section: Discussionmentioning
confidence: 96%
“…Our intervention was not associated with an improvement in growth monitoring accuracy. Improving growth monitoring interpretation accuracy has been found to be difficult in other studies (Mutoro & Wright, 2013) and might be explained by the quality of training or even the experience in practicing interpretation (Ezeofor et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Research among these populations of children in sub-Saharan Africa has shown high rates of stunting, wasting and underweight that are often at least double national prevalence (Kirk et al, 2017;Tann et al, 2018;Van den Boogaard et al, 2017). Although optimal weight gain in healthy, term infants has been studied and defined, there are no currently accepted international standards of how to monitor growth in premature infants, with a variety of methods used, including grams per day, grams per kilogram per day and z-scores (Fenton et al, 2017). Additionally, there is no single currently accepted standard growth chart for use in infants born prematurely.…”
Section: Introductionmentioning
confidence: 99%